The nucleotide sequences of 5S rRNAs from two red algae, Gracilaria compressa and Porphyra tenera. - Lim, B L (1983)
The nucleotide sequences of 5S rRNA from two red algae, Gracilaria compressa and Porphyra tenera have been determined. The two 5S rRNAs are fairly dissimilar to each other in their sequences (65% identity), although they are both composed of 121 nucleotides. Their secondary structures are generally of the eukaryotic with a prokaryotic characteristic. Judged from the 5S rRNA sequence data, the red algae are phylogenically distinct from green and brown algae, and they, Porphyra in particular, are evolutionally most ancient among the eukaryotes of which 5S rRNA sequence has been determined.